Intrinsically Disordered Protein Ensembles Shape Evolutionary Rates Revealing Conformational Patterns. Issue 3 (5th February 2021) - Palopoli, Nicolas; Marchetti, Julia; Monzon, Alexander M.; Zea, Diego J.; Tosatto, Silvio C.E.; Fornasari, Maria S.; Parisi, Gustavo
Graphical abstract: Highlights: Intrinsically disordered proteins evolve under heterogeneous site-specific rates. This rate heterogeneity emerges from different constraints by inter-residue contacts. Evolutionary rates are better explained combining contacts from selected conformers. Proteins sharing structural arrangements show similar evolutionary rate profiles. Evolutionary rates could be used for assessing the conformational diversity of IDPs. Abstract: Intrinsically disordered proteins (IDPs) lack stable tertiary structure under physiological conditions. The unique composition and complex dynamical behaviour of IDPs make them a challenge for structural biology and molecular evolution studies. Using NMR ensembles, we found that IDPs evolve under a strong site-specific evolutionary rate heterogeneity, mainly originated by different constraints derived from their inter-residue contacts. Evolutionary rate profiles correlate with the experimentally observed conformational diversity of the protein, allowing the description of different conformational patterns possibly related to their structure-function relationships. The correlation between evolutionary rates and contact information improves when structural information is taken not from any individual conformer or the whole ensemble, but from combining a limited number of conformers. Our results suggest that residue contacts in disordered regions constrain evolutionary rates to conserve the dynamic behaviour of the ensemble and that evolutionary rates can be used as a proxy for the conformational diversity of IDPs.